Recrystallization of Ni-based superalloy after cold deformation - Torkar, Matjaž (Kovine zlitine tehnologije, 1993)
The strain hardening and isothermal recrystallization after cold deformation of Ni-based superalloy was investigated. Cold deformation below 10% and annealing temperature above 1050°C promote the growth of recrystallized grains. A cold deformation, not lower than 10% and annealing between 1000°C and 1050°C for 30 minutes, produce fine recrystallized grains.
Keywords: zlitine; nikljeva superzlitina; deformacija materiala; rekristalizacija